Chapter 4 - Organic nanocarriers for brain drug delivery - Lúcio, Marlene (2021)
Although the blood–brain barrier remains a major barrier to drug delivery, organic nanocarriers (ONCs) have been demonstrated to be effective in targeting and delivering therapeutic agents to the brain and have provided promising preclinical outcomes. Because of their favourable physicochemical properties, such as biocompatible composition, nanometric dimensions, large surface area compared to volume and easily tuneable surfaces, ONCs have proven to be excellent transport vehicles capable of prolonging drug (or other therapeutic agents) circulation time and of addressing the challenges posed by numerous diseases affecting the brain.This chapter presents an overview of the different types of ONCs for brain delivery, including a description of their advantages and disadvantages, and a set of preclinical studies illustrating the most effective strategies for effective brain distribution. Biodegradation and bioelimination issues and future challenges for effective clinical translation are also addressed.